1993
DOI: 10.1099/00222615-39-6-440
|View full text |Cite
|
Sign up to set email alerts
|

The agglutination of  -haemolytic streptococci by lectins

Abstract: Summary. The ability of 25 lectins, isolated from different plants and fungi, to agglutinate 95 clinical isolates of P-haemolytic streptococci was examined. Cell suspensions were untreated, trypsin-treated or boiled at pH 2.0. None of the 95 untreated cell suspensions gave a visible reaction with any of the lectins. When the cells were trypsinised, 42 strains were agglutinated with one or more lectin and after boiling at pH 2, all the strains were agglutinated. After treatment with trypsin, 20 different agglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…However, bovine and human GBS strains did agglutinate with lectins when the bacteria were treated with trypsin, as shown in Table 3. In agreement with our findings, Kellens et al (1993) have reported that of 95 untreated b-haemolytic streptococci, none gave a visible reaction with any of the lectins tested, whereas 42 strains agglutinated with one or more lectin when the cells were treated with trypsin. The results suggest that certain adhesins are exposed after the bacteria have been treated with trypsin.…”
Section: Lectin-agglutination Test Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, bovine and human GBS strains did agglutinate with lectins when the bacteria were treated with trypsin, as shown in Table 3. In agreement with our findings, Kellens et al (1993) have reported that of 95 untreated b-haemolytic streptococci, none gave a visible reaction with any of the lectins tested, whereas 42 strains agglutinated with one or more lectin when the cells were treated with trypsin. The results suggest that certain adhesins are exposed after the bacteria have been treated with trypsin.…”
Section: Lectin-agglutination Test Resultssupporting
confidence: 93%
“…This has often been applied to the identification and characterization of microorganisms, exploiting the specificity of binding to cell surface sugars (Ottensooser et al, 1974;Slifkin & Cumbie, 1987;Kellens et al, 1993). In the present study, none of the GBS strains agglutinated with the lectins used.…”
Section: Lectin-agglutination Test Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Glycoconjugate agglutination test was performed by modification of the method described by Kellens et al (1993). In brief, bacterial cells were grown in three sets of 20 ml each in nutrient broth for 6 h at 37°C.…”
Section: Bacterial Glycoconjugates Agglutination Testmentioning
confidence: 99%
“…The extraction or enzymic treatment of streptococci may be expected to alter lectin aggregation patterns [4,[34][35][36][37][38], as streptococcal surfaces possess both hydrophobic and hydrophilic molecules [36]. Proteases might be expected to remove proteins, leaving exposed PG and group polysaccharides, while sonication would remove adventitiously bound medium components or non-c oval ently bound secreted molecules .…”
Section: Discussionmentioning
confidence: 99%